Effects of copper citrate as a defoliant in nursery fruit stock production - Gavrilović, Veljko M; Milićević, Zoran; Aleksić, Goran A; Starović, Mira S; Živković, Svetlana T; Stošić, Stefan S; Kuzmanović, Slobodan T (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The effects of copper citrate on defoliation of one year old fruit stocks in a nursery are presented in this paper. The investigation aimed to evaluate the defoliation efficacy of copper citrate as a new formulation, compared with other compounds recommended for that purpose. Field trials were conducted in the region of Trstenik, a center of nursery production in Serbia in 2016 and 2017. Two years of investigation showed that copper citrate could be used as an efficient compound for defoliation in nursery production. A stronger defoliation effect was observed on plum stocks, compared to apple stocks. Better results were achieved with the highest concentration of copper citrate (2%), while the effectiveness decreased with lower concentrations (0.5%, 1.0% and 1.5%). Defoliation degree on nursery apple stocks after treatment with 2.0% concentration of copper citrate varied from 80.6% to 95.6%, while it reached 100% on plum stocks.
Keywords: Copper; Defoliation; Nursery production; Fruit stocks